Perancangan Storyboard Motion Graphic Kesiapan Kerja Pada Perkembangan Artificial Intelligence - Bisyri Musthofa; Diana Aqidatun Nisa; Aryo Bayu Wibisono (UNIVERSITAS STEKOM, 2025)
The development of AI has fundamentally transformed the professional ecosystem, creating a series of contemporary challenges for Generation Z preparing to enter the work arena. This study focuses on the development of motion graphic storyboards as an educational instrument to enhance Generation Z's employability capabilities for the AI era. Implementing a hybrid research methodology, data collection was conducted through digital surveys and in-depth dialog with experts to explore perceptions on the implications of AI on employment and the strategic competencies needed to adapt. The research findings indicate that Generation Z shows substantial awareness of the urgency of skills upgrading and transfer, although there is still a lack of clarity in understanding the concrete consequences of AI on future employment prospects. The motion graphic design developed presents an adaptive approach through an engaging storyline, narrative visualization, and interactive character elements, with an emphasis on the concepts of T-Shaped Skills and Transferable Skills. The research concludes that professional readiness in the era of AI digitalization requires not only technological understanding, but also adaptive flexibility, creativity, and synergy between human capacity and digital systems. Motion graphics were identified as the optimal medium to convey knowledge and strengthen Generation Z's position in anticipating future professional dynamics.